(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The article addresses the issue of integrating elements of sports swimming into the general physical training of schoolchildren. The relevance of the topic is emphasized by the need to improve the physical fitness of students, especially given the poor health of many young people today. Competitive swimming, with its unique properties, is an effective way to develop important physical qualities such as endurance, strength, flexibility, and coordination. However, the problem of insufficient implementation of swimming in school physical education programs remains a pressing concern. The study aims to substantiate the effectiveness of using sports swimming elements to develop students’ physical qualities and to provide methodological recommendations for their integration into the educational process. The objectives include analyzing current scientific approaches to swimming in school physical education, assessing the fitness level of students engaged in swimming, and developing practical recommendations for teachers. The study confirms that regular swimming lessons improve the physical performance of schoolchildren, enhancing their endurance and coordination. Students who swim perform better than those who do not practice this sport. The article also provides methodological recommendations for incorporating swimming elements into the school physical education program. Additionally, the importance of integrating swimming into physical training is discussed, particularly in the context of modern teaching methods and limitations due to school infrastructure. It highlights the need to adapt lessons in schools without swimming pool access by using exercises that imitate swimming strokes. Furthermore, the article explores ways to motivate students to swim through extracurricular activities and school competitions. Such strategies will promote not only physical development but also a healthy lifestyle among young people.